Activities of Tobolsk Military-Industrial Committee during the West-Siberian Peasant Revolt of 1921 - V. V. Tsys (Научный диалог, 2017)
Certain aspects of the economic policy of the participants of the West-Siberian peasant revolt of 1921 are covered, the largest in the history of Soviet Russia Soviet anti-bolshevik armed uprising. Organizations involved in the management of industrial enterprises controlled by the rebels territory are characterized. Special attention is paid to the activities of the Tobolsk Military-Industrial Committee. The main directions of its work include: registration and distribution at the disposal of the insurgents of resources, mobilization of skilled manpower in the enterprises engaged in providing “partisans,” the introduction of measures to stimulate productivity, restore the industry to increase supply in the people’s army. Statistics of the production of clothing and shoes for the military is given. It is noted that as a result the Tobolsk Military-Industrial Committee was able to produce uniforms and shoes in sizes corresponding to the objective possibilities of the local handicraft industry. It is concluded that the democratic economic policy officially proclaimed by rebels because of the intensification of the onslaught from the advancing Red Army had folded, there was a transition to a system of more stringent measures, in some degree resembling war communism rejected by rebels.